LEGAL EXPLANATION ON THE IMPLEMENTATION OF COMMUNITY ACTIVITIES RESTRICTIONS (PPKM) TO REDUCE THE SPREAD OF COVID-19 IN INDRA MAKMU DISTRICT, EAST ACEH REGENCY - Zuleha; Fatimah; Nur Asyiah (LPPM dan PM Universitas Samudra, 2021)
The implementation of restrictions on community activities, often called Micro PPKM, is carried out in a limited manner in several cities/districts with the aim of reducing the spread of Covid-19 to the village/gampong level and seeking to increase the community's economy slowly and gradually. Micro PPKM is regulated by the issuance of the Minister of Home Affairs Instruction Number 01 of 2021 on January 6 and is enforced from January 11-25 and extended until March 2021. Prior to PPKM Micro, PPKM has been implemented to reduce the spread of Covid-19. Meanwhile, Aceh Province applies restrictions on micro community activities (PPKM) for the period 6-19 April 2021. Micro community activity restrictions (PPKM) are implemented by considering areas that have high risk and become the epicenter of an increase in Covid-19 cases. Indra Makmu Sub-district, which is East Aceh Regency, has implemented a Micro PPKM policy so that the impact of the spread of Covid-19 does not expand which causes the decline in the economic sector and other multidimensional impacts..